Ethnographies of Conferences and Trade Fairs : Shaping Industries, Creating Professionals - Høyer Leivestad, Hege; Nyqvist, Anette (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This anthology is an attempt to make sense of conferences and trade fairs as phenomena in contemporary society. The authors describe how these large-scale professional gatherings have become key sites for making and negotiating both industries and individual professions. In fact, during the past few decades, conferences and trade fairs have become a significant global industry in their own right. The editors assert that large-scale professional gatherings are remarkable events that require deeper analysis and scholarly attention. .